Anti-hyperglycemic and hypolipidemic effects of Saraca asoca (Roxb.) Wild. flowers in alloxan-treated diabetic rats - Ellappan Thilagam; Kumarappan Chidambaram; Chinthamreddy Raviteja; Thalu Vahana; Parameshwaran Vasudevan (GarVal Editorial Ltda., 2021)
Context: Saraca asoca (Leguminosae) has been widely used in the Ayurvedic system of medicine for various ailments, and it has been used to treat diabetes as a folk medicine. Aims: To investigate the anti-hyperglycemic and anti-hyperlipidemic effect of ethanolic extracts of S. asoca (EESA) flowers in alloxan-induced diabetic rats. Methods: The anti-hyperglycemic activity of EESA was evaluated by using normal and alloxan-induced (120 mg/kg, i.p.) diabetic rats. In the sub-chronic animal model of diabetes mellitus, EESA was orally administered to normal and alloxan-induced-diabetic rats at doses of 200 and 400 mg/kg p.o. per day for 28 days. Results: Fasting blood glucose (FBG), insulin, glycated hemoglobin (HbA1c) levels, lipid profiles, alkaline phosphatase (ALP), and body weights were monitored at the end of 28 days in the EESA treated diabetic rats. The anti-hyperglycemic effect of EESA was more pronounced at the doses of 200 and 400 mg/kg in alloxan-treated diabetic rats as compared with vehicle-treated rats. EESA also showed a significant (p<0.05) increase in serum insulin levels and body weights, while there was a significant reduction in the levels of ALP, HbA1c, serum triglyceride and total cholesterol. EESA also showed a significant anti-hyperlipidemic effect, as evidenced by the increased HDL-c level of alloxan-induced diabetic rats. Conclusions: The results of the current investigation indicate that EESA possesses a significant anti-hyperglycemic effect and anti-hyperlipidemic effect.